2019
DOI: 10.5120/ijca2019918292
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Multiple Objects Tracking in Video Analytics

Abstract: Multiple object tracking is being used for many applications nowdays such as automated surveillance, Robotics,self driving cars,medical and many more. There have been continuous improvements in existing state of art MOT(multiple object tracking) methods through many methods and global optimization techniques.This paper focuses on various MOT techniques and how to achieve speedup and efficiency using MOT methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Aftab Alam et al provided a review on video big data analytics in the cloud and proposed a service-oriented architecture bridging the gap among large-scale video analytics challenges, big data solutions, and cloud computing [28]. Anjali et al (2019) conducted a survey on multiple object tracking for fast and parallel video processing in MapReduce with the Amazon EC2 Cloud [29]. The results showed that for a large number of videos, the computational speed is faster and the performance is higher when using a fully parallel technique in comparison to a partially parallel technique.…”
Section: State Of the Art Overviewmentioning
confidence: 99%
“…Aftab Alam et al provided a review on video big data analytics in the cloud and proposed a service-oriented architecture bridging the gap among large-scale video analytics challenges, big data solutions, and cloud computing [28]. Anjali et al (2019) conducted a survey on multiple object tracking for fast and parallel video processing in MapReduce with the Amazon EC2 Cloud [29]. The results showed that for a large number of videos, the computational speed is faster and the performance is higher when using a fully parallel technique in comparison to a partially parallel technique.…”
Section: State Of the Art Overviewmentioning
confidence: 99%